Klinisk fagring som ein kompetanseutviklande metode i kommunehelsetenesta - sjukepleiarar og leiarar sine erfaringar - Hynne, Astrid Bjørnerheim; Torjuul, Kirsti; Paulsen, Bente (Nordisk tidsskrift for helseforskning, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 14.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN"><span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 14.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN"><span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The purpose of this study was to investigate the experiences of nurses and managers of a clinical circle as a method of competence development<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">, and the way working conditions <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">and <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">contextual factor<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">s<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> in the <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">municipality<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> affected the process of learning and <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">cooperation between nurses and managers<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">.<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Focus group interviews were conducted with five nurses and five managers. The interviews that were analyzed using qualitative content analysis resulted in three main<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">categories:<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> cooperation across different units, shared clinical theme, and <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">contextual factor<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">s. The findings indicate that participating in a clinical circle provide nurses with opportunities to develop their clinical competence through sharing knowledge and experiences, and by searching, assessing and implementing research findings into practice. In order to establish and sustain a clinical circle, the findings indicate that it may be useful to <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">prearrange contextual factor<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">s, such as leadership expectancy, and <span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">time<span style="font-family: 'Times New Roman',serif; font-size: 12pt; mso-bidi-font-size: 11.0pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">reserved for clinical circle work.